Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Relawan, Studi Kasus Pada Komunitas Call Center - Vernando, Alexander Nova; Fajarsari, Hesti; Kaharudin, Erlitawati; Saptyana, Riska Fita; Fajrul, Muh. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The aim of this research is to examine the influence of work motivation and job satisfaction on the performance of 112 call center community volunteers. Data was collected using a questionnaire. In total, 30 respondents were collected, then the data was analyzed using IBM SPSS Statistics 26 software. This type of research includes quantitative descriptive research. The research was conducted at the Semarang city communications and information department for approximately 3 months, with primary data sources and secondary data. The sample population of all volunteers from the 112 Semarang call center community in the Semarang city communications and information department was 30 people. Carried out using observation data collection methods, questionnaires, documentation and literature study. Test instrument validity and reliability. Hypothesis test, F test, t test, and determinant test. The results of the research show that work motivation job satisfaction simultaneously have a significant influence on the performance of the 112 Semarang call center community volunteers in the Semarang city communications and information services department. The results of this research show that work motivation and job satisfaction have a positive effect on the performance of call center 112 community volunteers.